Combination of transcriptomic, biochemical, and physiological analyses reveals sugar metabolism in Camellia drupifera fruit at different developmental stages - Liu, Zhen; Shen, Chunhui; Chen, Ruifan; Fu, Zhiqiang; Deng, Xiaomei; Xi, Ruchun (Frontiers in Plant Science, 2024)
Camellia drupifera, a significant woody oil crop in southern China, produces oil from its fruit seeds. Understanding sugar metabolism enzyme regulation is crucial for sugar accumulation and oil synthesis in fruit organs. This study examines the dynamic changes in sugar metabolism across four developmental stages of C. drupifera fruits, from rapid fruit enlargement to oil conversion. We analyzed sugar content, enzyme activity, and transcriptomic data to identify key periods and mechanisms involved in sugar metabolism. Our findings indicate that photosynthetic products are rapidly transported from leaves to fruit organs after synthesis, with transport efficiency decreasing significantly after 48 hours. September was identified as a critical period for oil conversion, during which the highest sucrose levels and SuSy-II enzyme activity were detected in the kernels. A positive correlation was found between high expression of ten genes related to sugar metabolism enzymes and sugar transport proteins and sucrose content. Notably, the expression levels of c158337.graph_c0 (SPS), c166323.graph_c0 (SuSy), c159295.graph_c0 (SUC2-like), and c156402.graph_c0 (SUC2-like) significantly increased during the oil conversion phase.These findings provide a crucial theoretical foundation for elucidating the molecular mechanisms of sugar metabolism in C. drupifera fruits, offering insights that could enhance its economic yield.